Challenges of temperature measurement during the friction stir welding process - Augustin, Silke; Fröhlich, Thomas; Krapf, Gunter; Bergmann, Jean-Pierre; Grätzel, Michael; Gerken, Jan Ansgar; Schmidt, Kiril (Видавництво Львівської політехніки, 2020)
The exact determination of the process zone temperature can be considered as an increasingly important role in the control and monitoring of the friction stir welding process (FSW). At present, temperature measurement is carried out with the aid of a temperature sensor integrated into the tool (usually thermocouples). Since these cannot be attached directly to the joining area, heat dissipation within the tool and to the environment cause measurement deviations as well as a time delay in the temperature measurement. The article describes a process and the challenges that arise in this process, how a direct temperature measurement during the process can be achieved by exploiting the thermoelectric effect between tool and workpiece, without changing the tool by introducing additional temperature sensors.
Keywords: Friction stir welding; Direct temperature measurement; Seebeck-Effect; Measurement errors